ADAPTING INTERACTIVE NEWS PROGRAM OF SUARA ANDA TO TEACH SPEAKING AT SENIOR HIGH SCHOOL - Albeni Yostija; Havid Ardi (Journal of English Language Teaching, 2013)
AbstractThis article discusses the use of techniques of adapting an interactive news program of "Suara Anda" in increasing student motivation for learning speaking at Senior high school. As programs, students are divided into several groups. Teachers provide multiple options displayed in power point news. One group choose one video and teachers play it. The group filed comments, suggestions or opinion about that news. Other groups may be added comment or suggestions. The process continues until all groups had a turn. At the end of the lesson the students were assigned to make a report or journal of the news.Key Words: speaking, interactive news program, suara anda